2015
DOI: 10.1007/s11270-015-2629-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Hexavalent Chromium Chemical Reduction with Sugarcane Molasses

Abstract: Sugarcane molasses, which is a kind of microbial carbon source, is a viscous by-product of the refining of sugarcane into sugar. However, experiments were designed to ascertain the mechanism and kinetics of Cr(VI) reduction with sugarcane molasses without adding microbes in aqueous solution. Results indicated that sugarcane molasses can reduce Cr(VI) to Cr(III) at pH values that range from 2.0 to 6.1 when no bioreduction occurs in the reaction. Furthermore, the reaction mechanism was proven to be that Cr(VI) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Sugarcane molasses has been successfully used in the remediation of groundwater contaminated Cr(VI) as a kind of organic materials. It was demonstrated that sugarcane molasses could reduce Cr(VI) to Cr(III) by chemical reduction and microbial reduction (Chen et al 2015(Chen et al , 2016. Chen et al (2017) discussed the reaction pathways and dynamics of chemical reduction of Cr(VI), and the reducing reaction of Cr(VI) could be described by a pseudo-first-order kinetic model.…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane molasses has been successfully used in the remediation of groundwater contaminated Cr(VI) as a kind of organic materials. It was demonstrated that sugarcane molasses could reduce Cr(VI) to Cr(III) by chemical reduction and microbial reduction (Chen et al 2015(Chen et al , 2016. Chen et al (2017) discussed the reaction pathways and dynamics of chemical reduction of Cr(VI), and the reducing reaction of Cr(VI) could be described by a pseudo-first-order kinetic model.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental results (Chen et al, 2015;Hansen et al, 2016) have established a rapid direct redox reaction when molasses is used as an electron donor and Cr(VI) is the contaminant, rather than the bio-mediated reaction previously posited. It is thus crucial to include this behavior in a model aimed at remediation design.…”
Section: Abiotic Reaction Of Electron Donor and Contaminantmentioning
confidence: 99%
“…Bioprecipitation, a process by which microbiological exudates react with metals to produce an insoluble compound, has been widely observed (Malik, 2004;Van Roy et al, 2006;Radhika et al, 2006) and has been noted by Wu et al (2010) as a remediation method. Bio-stimulants have also recently been shown to effectively reduce chromium through abiotic oxidation-reduction (redox) pathways (Chen et al, 2015;Hansen et al, 2016) and, after fermentation, for other metals (Hashim et al, 2011). Naturally, designing a remedial intervention using one of this family of techniques benefits greatly from the use of a multi-dimensional/multicomponent numerical model of groundwater flow, contaminant transport, and biogeochemical processes to evaluate different remediation strategies under varying field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, costs for some of these feedstocks (which serve as an electron donor) might become prohibitive in actual field applications. The use of industrial-grade molasses may provide a more cost-effective alternative to any of the above-mentioned carbon and energy sources [21][22][23][24][25]. According to the literature, the treatment cost when using molasses (0.13 € (Kg molasses) −1 in Greece) amounts to about 0.39 € (m −3 of wastewater) [25].…”
Section: Introductionmentioning
confidence: 99%